Relationship Between Serum Vitamin D and Perirenal Fat Thickness in Patients with Metabolic Syndrome in Community - Zhang HX; Zhai L; Gao Z; Yuan J (Diabetes, Metabolic Syndrome and Obesity, 2022)
Hong-Xia Zhang,1 Lu Zhai,1 Zhixiang Gao,2 Jie Yuan3 1Department of Endocrinology, Shanxi Provincial People’s Hospital, Taiyuan, People’ s Republic of China; 2Department of Ultrasonography, Shanxi Provincial People’s Hospital, Taiyuan, People’ s Republic of China; 3Department of Radiology, Shanxi Provincial People’s Hospital, Taiyuan, People’ s Republic of ChinaCorrespondence: Jie Yuan, Tel +86 13834164698, Email doctoryuang@163.comBackground: Visceral obesity is independently associated with hypovitaminosis D. Perirenal fat is a visceral fat type active in performing endocrine functions. However, the relationship between perirenal fat thickness (PrFT) and serum 25-hydroxy vitamin D [25(OH)D] is unclear. The aim of this study is to investigate the relationship between serum 25(OH)D and PrFT in patients with metabolic syndrome (MS) in the community.Methods: From May to September 2020, 332 MS subjects in Qinfengyuan and Dongfang communities in Taiyuan City, China were enrolled in an MS survey. All the participants completed the questionnaire survey and physical examination, and their fasting blood samples were collected for biochemical examination. Abdominal ultrasonography was performed to measure the perirenal fat thickness.Results: The mean serum 25(OH)D level for the 332 MS subjects was 13.5 ng/mL, the proportions of vitamin D deficiency [serum 25(OH)D < 20 ng/mL] and insufficiency [serum 25(OH)D = 20– 29.9 ng/mL] were 60.8% (202) and 24.4% (81), respectively. Among the hypovitaminosis D [serum 25(OH)D < 30 ng/mL] subjects, the prevalence of abdominal obesity (waist circumference ≥ 90cm for men and ≥ 80cm for women) is 61.1%. Pearson correlation analysis showed that lg25(OH)D was significantly and negatively associated with body mass index (BMI), waist circumference (W), total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), insulin resistance index (HOMA-IR), uric acid (UA)) and PrFT (all P< 0.05), and positively correlated with high-density lipoprotein cholesterol (HDL-C) (P< 0.05). Multivariate analysis showed that PrFT and HOMA-IR were independently correlated with 25(OH)D.Conclusion: In screening MS patients, approximately 85% of the community MS patients in Taiyuan had hypovitaminosis D; in which 3/5 is abdominal obesity. PrFT is an independent risk factor for hypovitaminosis D in MS subjects.Keywords: metabolic syndrome, 25(OH)D, hypovitaminosis D, perirenal fat thickness